Surgical interventions in velopharyngeal dysfunction: comparative perceptual speech and nasometric outcomes for three techniques - Ryan Instrum; Agnieszka Dzioba; Anne Dworschak-Stokan; Murad Husein (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background The aim of this study was to evaluate speech outcomes following surgical intervention for velopharyngeal dysfunction (VPD). Perceptual speech outcome data were subsequently analyzed in conjunction with patient factors such as congenital abnormalities, presence of cleft lip and/or palate, and age of repair. We hope to aid in the eventual creation of treatment algorithms for VPD, allowing practitioners to tailor surgical technique selection to patient factors. Methods A retrospective analysis was performed for all patients who underwent surgical correction of VPD at London Health Sciences Centre between the years 2005 and 2018. Two hundred and two consecutive VPD patients (median age 10.6 years) were followed for an average of 20.2 months after having undergone a superiorly based pharyngeal flap (121), Furlow palatoplasty (72), or sphincteroplasty (9). Speech outcomes were measured via the American Cleft Palate-Craniofacial Association (ACPA) perceptual speech assessment, and MacKay-Kummer Simplified Nasometric Assessment Procedures Revised (SNAP-R) was used to measure nasalence. Comparisons of mean preoperative and postoperative outcomes were made, as well as analyses regarding surgical procedure, syndrome, cleft status, and age. Results Mean perceptual scores improved significantly postoperatively (p < .0001), and successful perceptual resonance was identified in 86.1% patients (n = 174). Postoperative perceptual speech scores for three ACPA domains were superior with pharyngeal flap compared to both Furlow palatoplasty and sphincteroplasty ([hypernasality: p < .001, p < .02], [audible nasal emissions: p < .002, p < .05], [velopharyngeal function: p < .001, p < .05]). Success rate was higher in pharyngeal flap (94.2%) than in Furlow palatoplasty (75.0%, p < .001) or sphincter pharyngoplasty (66.7%, p < .001). No significant difference was identified in success rate based on syndrome or cleft status. Conclusion Operative management of VPD is highly effective in improving perceptual speech outcomes. Given proper patient selection, all three procedures are viable treatment options for VPD. For those patients identified as appropriate to undergo a pharyngeal flap, robust improvements in speech outcomes were observed. Graphical abstract